Penafsiran Sufistik Surat Al-Fatihah dalam Tafsir Tāj Al-Muslimîn dan Tafsir Al-Iklîl Karya KH Misbah Musthofa - Iskandar Iskandar (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2015)
The article explains the sufism tafsir of Surah Al-Fatihah in the tafsir of Tâj Al- Muslimîn and al-Iklîl written by KH. Misbah Musthofa by using tahlili method. The findings shows that 7 verses of Al-fâtihah have Sufism nuances, especially in verse 5, dealing with worship to Allah which consists of 3 levels; low, middle, and high worship. The tafsir of Tâj Al- Muslimîn and al-Iklîl, written by KH. Misbah Musthofa, have some strengths and flaws. The tafsir of Surah Al-Fatihah in Tâj Al- Muslimîn and al-Iklîl are still relevant in this modern era. It is proven by the explanation of the importance model of multi-dimension and multi-function of the human services. Still, from the aspect of the language, it needs some adjustment and modification. So that, to understand Al-Qur’an, as proposed by Muhammed Arkoun by using mystical analysis, such as: reading “ar-rahman ar-rahim”, we do not say or do the action, but we also create the action; hope, forgiveness, confession, or request.